Contemporary issues in database design and information systems development - Siau, Keng. (Hershey : IGI Publishing, 2007)
Presents the research ideas and topics on databases and software development. The chapters in this work provide a representation of research in various areas of the database and information systems development.
Includes bibliographical references and index.
Keywords: Database design; System design; Computers -- Desktop Applications -- Databases